Near-infra-red fluorescent chitosan oligosaccharide lactate for targeted cancer imaging and photothermal therapy - Sungsu Lee; Gayoung Jo; Jin Seok Jung; Dae Hyeok Yang; Hoon Hyun (Artificial Cells, Nanomedicine, and Biotechnology)
Photothermal therapy (PTT) is a promising approach for effective cancer treatment because of its non-invasive procedure, low toxicity to normal tissues, and high tumour ablation efficiency. Developing a PTT agent with precise tumour imaging capabilities is an essential prerequisite for effective PTT. In this study, we developed a bifunctional near-infra-red (NIR) fluorescent conjugate consisting of chitosan oligosaccharide lactate (COL) and the ZW800-1 NIR fluorophore (COL-ZW). We demonstrate that this conjugate is easy to use and that it is an effective theranostic agent for fluorescence-guided photothermal treatment. The temperature of COL-ZW increased by 62.3 °C after NIR laser irradiation (1.1 W/cm2) for 5 min in HT-29 tumour-bearing mice. The HT-29 tumours targeted by COL-ZW showed a remarkable decrease in tumour volume until a week after photothermal treatment. These in vivo results demonstrate that the bifunctional COL-ZW generates strong fluorescence and light-triggered PTT in tumour sites, indicating successful fluorescence-guided PTT. Importantly, no tumour recurrence or treatment-induced toxicity was observed after a single dose of COL-ZW with laser irradiation. Therefore, a combinatorial treatment with COL-ZW and NIR laser irradiation could serve as a promising strategy for photothermal cancer therapy.